Transformações no arranjo criminal e gestão dos conflitos nas periferias: um estudo sobre juventude e tráfico de drogas no contexto de disputas entre facções em Fortaleza (2015-2025) - Santiago Neto, João Pedro de (2025)
This thesis investigates the recent transformations in the criminal arrangement and conflict management in the urban peripheries of Fortaleza, Ceará, between 2015 and 2025. Based on a socio-anthropological approach — grounded in the analysis of documents, news reports, official data, ethnographic observation, and interviews with young people involved in the drug trade (“no corre”) — the study examines how the actions of armed collectives reshaped the retail drug market, redefined territorial borders, and decisively impacted youth trajectories in the urban margins of the city. The central hypothesis is that the intensification of disputes over drug trafficking control led to the growing presence of criminal factions in working-class neighborhoods, prompting local groups to align with larger collectives in search of protection, recognition, and access to resources. In this process, new forms of social control, violence regulation, and conflict resolution began to shape everyday life in the peripheries (Simmel, 1983). The thesis analyzes how youth engage in these dynamics, with special attention to the rise of Comando Vermelho (CV) and the episode known as the “Golpe de Estado,” which triggered the consolidation of Tudo Neutro (TDN) in the studied neighborhood. It explores how young people enter drug trafficking networks, participate in disputes, and take on strategic roles in mediating local tensions, operating in contexts marked by threats, constant surveillance, and instability. Drawing from their narratives and lived experiences, the study seeks to understand how they construct senses of belonging, activate loyalty codes, and assign meaning to experiences of violence and factional conflict. The findings reveal that the presence of criminal factions directly affects daily life in the peripheries, transforming practices of mobility, leisure, and social interaction among youth, while shaping ways of living, dreaming, and surviving in urban margins. This presence reconfigures community ties and life projects, understood as situated constructions marked by choices, constraints, and daily negotiations (Velho, 2003), while intensifying logics of surveillance and control over youth bodies, territories, and behaviors (Foucault, 1975). Finally, the thesis offers a critical reading of the rise of armed collectives, challenging reductionist views of criminal factions and analyzing their social, political, and subjective effects on the lives of marginalized youth. It contributes to the field of youth, violence, and urban crime studies in Brazil by revealing how criminal conflicts are produced, negotiated, and experienced in territories shaped by structural inequalities.